2003
DOI: 10.1086/345738
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Spectra of Population III Stars: Consequences for Cosmological Reionization

Abstract: We examine the significance of the first metal-free stars (Population III) for the cosmological reionization of H i and He ii. These stars have unusually hard spectra, with the integrated ionizing photon rates from a Population III stellar cluster for H i and He ii being 1.6 and 10 5 times stronger, respectively, than those from a Population II cluster. For the currently favored cosmology, we find that Population III stars alone can reionize H i at redshifts of z ' 9 and 4.7 and He ii at z ' 5:1 and 0.7 for co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 66 publications
1
84
1
Order By: Relevance
“…While the population of sources that reionized the Universe may have been discovered in high-redshift surveys, a definite conclusion is still premature. There is some evidence for a population of low-luminosity star-forming galaxies at redshifts as high as z Ӎ 8 -10 that may contribute substantially to the total budget of reionizing photons ͑Stark, Several semianalytic estimates for the expected contribution of galaxies to the reionization of both hydrogen and helium have been made ͑Haiman and Holder, 2003; Venkatesan et al, 2003;Haiman and Bryan, 2006;Shull and Venkatesan, 2008͒. The possible halo masses of the objects that dominate reionization cover a broad range, including systems as small as minihalos with masses M halo Ͻ 10 6 M ᭪ and virial temperatures T vir Ͻ 1000 K which would have so far evaded detection.…”
Section: Galaxiesmentioning
confidence: 99%
“…While the population of sources that reionized the Universe may have been discovered in high-redshift surveys, a definite conclusion is still premature. There is some evidence for a population of low-luminosity star-forming galaxies at redshifts as high as z Ӎ 8 -10 that may contribute substantially to the total budget of reionizing photons ͑Stark, Several semianalytic estimates for the expected contribution of galaxies to the reionization of both hydrogen and helium have been made ͑Haiman and Holder, 2003; Venkatesan et al, 2003;Haiman and Bryan, 2006;Shull and Venkatesan, 2008͒. The possible halo masses of the objects that dominate reionization cover a broad range, including systems as small as minihalos with masses M halo Ͻ 10 6 M ᭪ and virial temperatures T vir Ͻ 1000 K which would have so far evaded detection.…”
Section: Galaxiesmentioning
confidence: 99%
“…Among the relevant scientific issues are the star formation rate at high redshift (see, e.g., Springel & Hernquist 2003b), the epoch of reionization (see, e.g., Gnedin 2000;Fan et al 2000;Cen 2003;Venkatesan, Tumlinson, & Shull 2003;Sokasian et al 2003;Wyithe & Loeb 2003a), and the fate of high-redshift systems (White & Springel 1999). The statistical properties of early baryonic objects are of direct relevance to understanding the significance of the first stars to these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In most calculations of cosmological reionization, it has to be assumed that the product of star formation rates (SFRs) and hydrogen ionizing photon escape fraction is 0.01 (e.g., Gnedin 2000;Cen 2003aCen , 2003bWyithe & Loeb 2003a, 2003bVenkatesan et al 2003;Somerville et al 2003;Chiu et al 2003;Haiman & Holder 2003;Ciardi et al 2003;Sokasian et al 2003Sokasian et al , 2004Wyithe & Cen 2007;Srbinovsky & Wyithe 2008) in order to reionize the universe early enough to be consistent with the Wilkinson Microwave Anisotropy Probe (WMAP) observations (Spergel et al 2007;Komatsu et al 2009), if stars produce the majority of ionizing photons. Gnedin (2000) suggested that, based on Local Group dwarf galaxies, the SFRs at high redshift are ∼ 4%, consistent with theoretical works (e.g., Krumholz & McKee 2005;Krumholz & Tan 2007).…”
Section: Introductionmentioning
confidence: 99%